Unveiling Rudeness: Impoliteness Strategies Used by the Judge of America’s Got Talent - Kulsum, Umi; Nur Latifah (Alphabet, 2025)
Technological advancement and increasing cultural diversity lead to misunderstandings in communication. Therefore, individuals need to understand impoliteness strategies to prevent misunderstandings and by understanding impoliteness strategies to increase success in communication. This phenomenon is reflected in the American talent show, America's Got Talent, which illustrates how the judges' utterances are acts of impoliteness. This study examines the types of impoliteness strategies contained in the judges' utterances on America's Got Talent in 2023 using culpeper's theory. In addition, this study also analyzes the functions of these impoliteness strategies based on Culpeper's (2011) theory, focusing on what functions the judges use the impoliteness in the show. This study uses a descriptive qualitative method that aims to analyze examples of impoliteness strategies used in the judges' utterances. In this study, researchers found all types of impoliteness strategies by Culpeper's theory other than the Withhold politeness type. In addition, the researchers also found all the functions of impoliteness used by the judges on America's Got Talent.